2014
DOI: 10.1017/s1751731114001633
|View full text |Cite
|
Sign up to set email alerts
|

Farm characteristics related to on-farm cow mortality in dairy herds: a questionnaire study

Abstract: Dairy cow mortality is an important animal welfare issue that also causes financial losses. The objective of this study was to identify farm characteristics and herd management practices associated with high on-farm cow mortality in Swedish dairy herds. A postal questionnaire was sent to farmers that had either high or low mortality rates for 3 consecutive years. The questionnaire consisted of five sections: 'About the farm', 'Milking and housing', 'Feeding', 'Routines' and 'Lame and sick cows'. A total of 145… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
3
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 23 publications
1
14
3
2
Order By: Relevance
“…Other similarities were found within several variables describing herd levels of disease and illness, operation facilities and biosecurity practices. These findings agree with previous studies outside of the United States that suggest that mortality may be associated with greater rates of common production diseases, as well as physiologic stress linked to intensive management practices such as animal crowding and feeding high levels of concentrate (Norgaard et al, 1999;Thomsen et al, 2007;Alvåsen et al, 2014). While the Dairy 2002 and 2007 surveys had similarities, the Dairy 2007 survey data set expanded upon the findings from the Dairy 2002 survey data and resulted in a unique final model.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Other similarities were found within several variables describing herd levels of disease and illness, operation facilities and biosecurity practices. These findings agree with previous studies outside of the United States that suggest that mortality may be associated with greater rates of common production diseases, as well as physiologic stress linked to intensive management practices such as animal crowding and feeding high levels of concentrate (Norgaard et al, 1999;Thomsen et al, 2007;Alvåsen et al, 2014). While the Dairy 2002 and 2007 surveys had similarities, the Dairy 2007 survey data set expanded upon the findings from the Dairy 2002 survey data and resulted in a unique final model.…”
Section: Discussionsupporting
confidence: 87%
“…Rather, it highlights the continuum of health problems that can include these specific diseases and that indicate underlying management issues related to disease prevention. Although mastitis can predispose to other diseases such as metritis, displaced abomasums, ketosis and cystic ovaries (Gröhn et al, 2003), and infertility problems often follow such diseases (Harman et al, 1996;Gröhn and Rajala-Schultz, 2000), the issue at hand remains one of defining those specific management practices that eventuate in these poor outcomes including death (Alvåsen et al, 2014). Further, although culling lame and injured cows may preempt some individual cow deaths, a rise in such forced culling may be indicative of other underlying problems that eventuate in higher mortality levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Less intense production systems, lower animal density, and more time spent outdoors generally lead to higher animal welfare [59,60]. However, further research and improvements are needed to improve welfare in production systems considered more animal-friendly, as these sometimes have lower animal welfare than more conventional systems [60,61].…”
Section: Resource Utilization Within Productionmentioning
confidence: 99%
“…According to EFSA (Anon., 2009d), access to pasture reduces the risk for hoof diseases, lameness, teat tramping, mastitis, acute metritis, dystocia, ketosis, retained placenta and various bacterial infections. Danish and Swedish studies have also shown a reduced mortality risk in herds with more pasture access (Thomsen et al, 2007;Burow et al, 2011;Alvåsen et al, 2014). There is evidence that cattle prefer access to pasture, but this preference depends on the time of day and the weather conditions; cattle avoid bright sunshine and high temperatures (Legrand et al, 2009;Charlton et al, 2013).…”
Section: Confinement and Restricted Movementmentioning
confidence: 99%